2017
DOI: 10.1021/acsomega.7b00345
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Heteroarchitectures of Two-Dimensional MoS2@ One-Dimensional Brookite TiO2 Nanorods: Prominent Electron Emitters for Displays

Abstract: We report comparative field electron emission (FE) studies on a large-area array of two-dimensional MoS 2 -coated @ one-dimensional (1D) brookite (β) TiO 2 nanorods synthesized on Si substrate utilizing hot-filament metal vapor deposition technique and pulsed laser deposition method, independently. The 10 nm wide and 760 nm long 1D β-TiO 2 nanorods were coated with MoS 2 layers of thickness ∼4 (±2), 20 (±3), and 40 (±3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…The binding energies of 163.5 and 162.3 eV are associated with the S 2p 1/2 and S 2p 3/2 of S 2− anion in MoS 2 . Remarkably, the energy separation in Mo (3p 3/2 and 3p 5/2 ) and S (2p 1/2 and 2p 3/2 ) orbit are 3.2 eV (<3.3 eV) and 1.2 eV (<1.4 eV), respectively, due to the formation of MoS 2 . For the UMT‐0.14 hybrid, however, the binding energies of the Mo 4+ species in the composite obviously are shifted to lower binding energies by 1.0 (Mo 3p 3/2 ) and 0.9 eV (Mo 3p 5/2 ), which are caused by the injected electrons transfer to the d orbital of the Mo centre in the transition metal dichalcogenide.…”
Section: Resultssupporting
confidence: 69%
“…The binding energies of 163.5 and 162.3 eV are associated with the S 2p 1/2 and S 2p 3/2 of S 2− anion in MoS 2 . Remarkably, the energy separation in Mo (3p 3/2 and 3p 5/2 ) and S (2p 1/2 and 2p 3/2 ) orbit are 3.2 eV (<3.3 eV) and 1.2 eV (<1.4 eV), respectively, due to the formation of MoS 2 . For the UMT‐0.14 hybrid, however, the binding energies of the Mo 4+ species in the composite obviously are shifted to lower binding energies by 1.0 (Mo 3p 3/2 ) and 0.9 eV (Mo 3p 5/2 ), which are caused by the injected electrons transfer to the d orbital of the Mo centre in the transition metal dichalcogenide.…”
Section: Resultssupporting
confidence: 69%
“…However higher binding energy peak observed at 531.1 represents the surface contamination or presence of hydroxyl (-OH) groups. [38][39][40][41] The close analysis of decomposed XPS spectrum revealed that the intensity of the peaks assigned to core levels of Ni 3+ (2p 3/2 ) and Ni 3+ (2p 1/2 ) is larger than that of core levels Ni 2+ (2p 3/ 2 ) and Ni 2+ (2p 1/2 ) at decomposition temperature of 400 and 500 C. However, the intensity of the peaks of Ni 2+ (2p 3/2 ) and Ni 2+ (2p 1/2 ) core levels has increased than that of peaks of Ni 3+ (2p 3/2 ) and Ni 3+ (2p 1/2 ) core levels aer the decomposition temperature of 700 C and are continued to increase for the temperature of 1100 C. The intensity ratio obtained for the peaks of the Ni 2+ (2p 3/2 ) and Ni 3+ (2p 3/2 ) core levels (i.e. Ni 2+ / Ni 3+ ) has increased from 0.85 (AE0.03) to 1.23 (AE0.03) with an increase in the temperature from 400 to 1100 C. Moreover, the variation in the intensity of the core levels assigned to the Ni 2+ and Ni 3+ is more apparent at decomposition temperature of 500 and 700 C in Fig.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…Due to their exposed sharp edges, un-stacked morphology and high aspect ratio they are less affected by Joule heating [ 11 ]. In the past few years, FE measurements on different MoS 2 morphologies, such as horizontally arranged (with a few protruding portions) MoS 2 [ 12 ], sparsely distributed vertically aligned MoS 2 NSs [ 9 ], MoS 2 nanoflowers [ 13 ] and MoS 2 nano-heteroarchitectures [ 14 ] have been reported. The semiconducting MoS 2 NSs with exposed edges could significantly enhance the FE properties [ 9 ].…”
Section: Introductionmentioning
confidence: 99%